2017
DOI: 10.1016/j.seizure.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Convulsive status epilepticus in a quaternary hospital paediatric intensive care unit (PICU) in South Africa: An 8 year review

Abstract: The high burden of infection related CSE is associated with high morbidity and mortality rates in contrast to the rates in developed countries. This highlights the need for early recognition and treatment of underlying conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
7
2
Order By: Relevance
“…38 patients had seizures lasting for 60 mins to 24 h and 7 patients for more than 24 h. This is because patients from remote rural areas are referred to our hospital for management of SE and at times, poor transportation facilities lead to a delay in initiation of treatment. Seizure characteristics such as duration, number of drugs needed to achieve control and presence of recurrent seizures had an association with outcome as seen in multiple studies [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 patients had seizures lasting for 60 mins to 24 h and 7 patients for more than 24 h. This is because patients from remote rural areas are referred to our hospital for management of SE and at times, poor transportation facilities lead to a delay in initiation of treatment. Seizure characteristics such as duration, number of drugs needed to achieve control and presence of recurrent seizures had an association with outcome as seen in multiple studies [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [ 18 ] reported that 1% to 12% of children from countries in the developed world presenting with SE have infectious cause as compared to 28.6% seen in our study. An 8-year review of PICU admissions in a hospital in South Africa [ 17 ] showed an infective cause in 43% cases, whereas an Indian study conducted in Bihar [ 16 ] showed 38.5% cases. Thus, infections are still a major cause of pediatric SE in developing countries like India and the scope of preventive strategies in reducing its burden is large.…”
Section: Discussionmentioning
confidence: 99%
“…Within the acute symptomatic etiology, CNS infections (e.g. herpes simplex virus (HSV), HIV, neurocysticercosis, malaria, tuberculosis), viral/autoimmune encephalitis and meningitis are common causes [7,[24][25][26][27][28][29][30].…”
Section: Etiologymentioning
confidence: 99%
“…The incidence of CSE is the highest among children and the elderly [9,10,11]. Of importance, over 80.0% of children with epilepsy are located in resource-limited countries [12] and CSE is the second most common outpatient neuropsychiatric diagnosis in Mozambique [13]. Even though CSE is a worldwide problem, optimal care is hampered by multiple barriers in resource-limited countries.…”
Section: Introductionmentioning
confidence: 99%
“…These barriers include the unavailability of ASMs, patient transportation delays, low quality health care infrastructures and the potential lack of a CSE treatment protocol [6,14,15]. Especially in resource-limited countries, the lack of clear treatment strategies (prehospital and hospital management) could induce unnecessary treatment delays, extra morbidities and higher mortality rates [12,16].…”
Section: Introductionmentioning
confidence: 99%